New media at mga sanaysay sa platitude ng bagong objek ng media at mediasyon sa Filipinas - Tolentino, Rolando B.; University of Santo Tomas Publishing House (Manila University of Santo Tomas Publishing House, 2016)
Essays on the use of new media platforms in the Philippines.
Includes bibliographical references and index.
In Filipino.
Keywords: New media art -- Philippines; Art and technology -- Philippines; Multiculturalism -- Philippines